PERBANDINGAN TINGKAT PENGHASILAN ANTARA LAKI-LAKI LAJANG DAN LAKI-LAKI MENIKAH PERSPEKTIF ISLAM (STUDI PADA PENDUDUK LAKI-LAKI INDONESIA BERDASARKAN DATA INDONESIAN FAMILY LIFE SURVEY TAHUN 2007 DAN 2014) - Frendi Prayogo; Noven Suprayogi (Universitas Airlangga, 2019)
Marriage is worship that exemplified by Rasulullah PBUH. The purpose of marriage is making a happy family. However, economic barriers are commonly used to delay marriage even though God promises wealth for married people. The purpose of this study was to analyze the ratio of income levels between single men and married men in Indonesia based on the Islamic perspective. Subjects in this study were individuals in households aged 15 years or older who were individuals in the Indonesian Family Life Survey (IFLS) study of 24 provinces in Indonesia. This research is a quantitative research by using Mann-Whitney and Wilcoxon test. The sampling used is the documentation technique. The data used are taken from the IFLS-4 data in 2007 and IFLS-5 in 2014. The results showed that there was a significant difference in income level between a group of single men and a group of married men and there was a significant difference in income level between before and after marriage in the same sample.Keywords: Single, Married, Income Level, Islamic PerspectiveREFERENCESAbdurahman. 1992. Kompilasi Hukum Islam di Indonesia. Jakarta: Akademika PressindoAbul Hasan, Muslim. Tanpa Tahun. Shahih Muslim II. Semarang: Toha PutraAhituv, Avner dan Robert I Lerman. 2007. How Do Marital Status, Work Effort, And Wage Rates Interact?. Demography, 44 (3): s623–647Al Bigha, Mushthafa. 2008. Fikih Manhaji. Terjemahan oleh Misran. 2012. Yogyakarta. Darul UswahAtabik, Ahmad dan Khoridatul Mudhilah. 2014. Pernikahan dan Hikmahnya Perspektif Islam. Yudisia, 5 (2): 286-316Dalmia, Sonia, dkk. 2016. Marriage and Men’s Earnings: Specialization and Cross-Productivity Effects. Eastern Economic Journal. (42): 335-348Departemen Agama Republik Indonesia. 2007. Mushaf Al Qur’an Terjemah. Jakarta: Tim Penerbitan Gema Insani Al HudaDiana, Rachmy. 2008. Penundaan Pernikahan: Perspektif Islam dan Psikologi. Jurnal Psikologi, 1 (2): 163-182Dunga, Steven Henry. 2017. A Gender and Marital Status Analysis of Household Income in A Low-Income Township. Studia Universitatis Babes-Bolyai Oeconomica, 62 (1): 20-30Furqon. 1999. Statistika Terapan untuk Penelitian. Bandung: Alfabeta.Ghazaly, Hamid. Tanpa Tahun. Ihya’ Ulumuddin. Terjemahan oleh Ismail Yakub. 1971. Beirut : Dar al FikrHewitt, Belinda, dkk. 2002. Marriage and Money: The Impact of Marriage on Men’s and Women’s Earnings. Makalah dipresentasikan pada Australian Sociological Conference, Brisbane.Hewitt, Belinda, dkk. 2002. Marriage and Money: The Impact of Marriage on Men’s and Women’s Earnings. Makalah disajikan dalam Australian Sociological Conference. Brisbane.Ikatan Akuntan Indonesia. 2009. Kerangka Dasar Penyusunan dan Penyajian Laporan Keuangan. Jakarta: Salemba Empat____________________. 2009. Standar Akuntansi Keuangan (SAK) Tahun 2009. Jakarta: Salemba EmpatIndriantoro, Nur dan Bambang Supomo. 2002. Metodologi Penelitian Bisnis. Yogyakarta: Penerbit BPFE Yogyakarta Ismatulloh, A. M.. 2015. Konsep Sakinah, Mawaddah, dan Rahmah dalam Al Qur’an (Perspektif Penafsiran Kitab Al Qur’an dan Tafsirnya). Jurnal Mazahib, (Online), Jilid XIV, No. 1, (https://media.neliti.com, diakses 19 Agustus 2017).Iswati, Sri dan Muslich Anshori. 2009. Buku Ajar Metodologi Penelitian Kuantitaif. Surabaya: Airlangga University PressKamal, Muchtar. 2004. Asas-asas Hukum Islam Tentang Perkawinan. Jakarta: Bulan BintangKBBI, 2017. Kamus Besar Bahasa Indonesia (KBBI), (Online), (http://kbbi.web.id/pusat, diakses 21 Agustus 2017).Kuheba, Jefier Andrew, dkk. 2016. Perbandingan Penghasilan Usaha Tani Campuran Berdasarkan Pengelompokan Jenis Tanaman. Agri-Sosioekonomi Unsrat, 12 (2A): 77 - 90Kuheba, Jefier Andrew. 2016. Perbandingan Pendapatan Usahatani Campuran Berdasarkan Pengelompokan Jenis Tanaman. Jurnal Agri-Sosiologi Unsrat, 12 (2A): 77-99Kurniawati, Novi. 2012. Pernikahan Usia Dini dan Posisi Perempuan dalam Keluarga. Skripsi Tidak Diterbitkan. Bandung Universitas Islam BandungLoughran, David S dan Julie M. Zissimopoulos. 2004. Are There Gains to Delaying Marriage? The Effect of Age at First Marriage on Career Development and Wages. Makalah merupakan bagian dari riset RAND Labor and Population working paper series, November 8, Santa Monica.Mahalli, A. Mudjab. 2003. Menikahlah, Engkau Menjadi Kaya. Cetakan Ketiga. Yogyakarta: Mitra PustakaMunawwaroh, Latifah. 2017. Penggunaan Kaidah Fiqhiyyah “Al-Khuruj Min Al-Khilaf Mustahab” Terkait Bab Ibadah dalam Kitab I’anat Al Thalibin. Jurnal Nuansa, (Online), Jilid 14 No. 1, (https://ejournal.stainpamekasan.ac.id, diakses 19 Agustus 2017).Razaq, Abu Hafs. 1998. Panduan lengkap Nikah (dari “A” sampai “Z”). Terjemahan oleh Ahmad Saikhu. 2006. Bogor. Pustaka Ibnu KatsirRofiq, Ahmad. 2012. Hukum Perdata Islam di Indonesia. Edisi Revisi. Jakarta: Rajawali Pers.Sabiq, Sayyid. Tanpa Tahun. Fiqhus Sunnah Jilid 2. Terjemahan oleh Moh. Abidun. 2008. Jakarta: Pena Pundi AksaraSantrock, J. W. Tanpa Tahun. Adolescence. Terjemahan oleh Shinto B. Adelar dan SherlySari, Fitri. 2012. Kesiapan Menikah Pada Dewasa Muda dan Pengaruhnya terhadap Usia Menikah. Skripsi Tidak Diterbitkan. Bogor Ekologi Manusia Institut Pertanian BogorSasmita, Elvin. 2012. Menikahlah, Karena Allah Selalu Punya Rencana yang Jauh Lebih Baik. Kuliah Online Parenting Nabawiyah, (Online), (http://www.parentingnabawiyah.com, diakses 7 September 2017).Schoeni, Robert F. 1995. Marital Status and Earnings in developed Countries. J Popul Econ, 8:351-359Septiana, Ema dan Muhammad Syafiq. 2013. Identitas Lajang (Single Identity) dan Stigma: Studi Fenomologi Perempuan Lajang Di Surabaya. Jurnal Psikologi Teori & Terapan, 4 (1): 71 – 86Solimun. 2002. Multivariate Analysis: Structural Equation Modelling (SEM), Lisrel dan Amos. Malang: Penerbit Universitas Negeri MalangSriwidadi, Teguh. 2011. Penggunaan Uji Mann-Whitney pada Analisis Pengaruh Pelatihan Wiraniaga dalam Penjualan Produk Baru. Binus Business Review, 2 (2): 751-762Sugiyono. 2011. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: AlfabetaSyarifuddin, Amir. 2004. Hukum Perkawinan Islam Di Indonesia. Jakarta: Predana Media GroupTanau, Felinsa Oktora. 2016. Perbedaan Tingkat Kecenderungan Perilaku Altruisme pada Dewasa Awal dan Dewasa Madya. Skripsi Tidak Diterbitkan. Yogyakarta Psikologi Universitas Sanata DharmaUmam, Khairul. 2001. Ushul Fiqih. Bandung: Pustaka SetiaUndang-undang Nomor 1 Tahun 1974 Tentang PerkawinanUndang-Undang Republik Indonesia Nomor 36 Tahun 2008 tentang Perubahan Keempat atas Undang-Undang Nomor 7 Tahun 1984 tentang Pajak Penghasilan.Usamah, Abu Hafs. 2006. Panduan Lengkap Nikah. Terjemahan oleh Ahmad Saikhu. Cetakan Kelima. Bogor: Pustaka IlmuZagorsky, Jay L. 2005. Marriage and divorce’s impact on wealth. Journal of Sociology, 41(4): 406–424